2017
DOI: 10.4314/ahs.v17i3.15
|View full text |Cite
|
Sign up to set email alerts
|

HIV counseling and testing practices among clients presenting at a market HIV clinic in Kampala, Uganda: a cross-sectional study

Abstract: BackgroundUptake of HIV counseling and testing (HCT) among informal sector workers is not well documented.ObjectiveTo assess HCT practices among clients presenting for HIV services at a market HIV clinic in Kampala, Uganda.MethodsBetween August 1 and September 15, 2009, clients presenting for HIV services at a market HIV clinic were invited to participate in the study. Socio-demographic and HCT data were collected from consenting adults aged 16+ years. Descriptive statistics were performed using STATA version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…These repeat testers are people who already know their HIV status and they just want to confirm whether the first test they conducted was actually true, thus the low yield in that period. This finding was consistent with the findings of Matovu JKB et al in 2017 where they found that 73.7% of the market vendors who turned up for HIV test were those who had ever tested for HIV [12]. Factors associated with repeat HIV testing varies from place to place and dependent on the study method used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These repeat testers are people who already know their HIV status and they just want to confirm whether the first test they conducted was actually true, thus the low yield in that period. This finding was consistent with the findings of Matovu JKB et al in 2017 where they found that 73.7% of the market vendors who turned up for HIV test were those who had ever tested for HIV [12]. Factors associated with repeat HIV testing varies from place to place and dependent on the study method used.…”
Section: Discussionsupporting
confidence: 90%
“…Living with an HIV positive family member/friend and selfreported good health [13], need to confirm HIV diagnosis and belief that the previous test results were false [12], being a man having sex with men (MSM) or injection drug user (IDU) or having multiple sexual partners [14] were among the common factors identified as contributing to repeat tests in South Africa, Uganda and Croatia respectively. However, with the application of the double layered screening, there was a reduction in the proportion of repeat testers, with most of the clients who had turned up to repeat the HIV test before their due dates being turned away to wait to repeat the test either after 3 months for those at high risk of infection or after 12months for those at low risks, and only offering HTS to the repeat testers at substantial risk of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the people of this group were more likely to engage in some high-risk sexual behaviors, and they were at a higher risk of HIV infection. This phenomenon could be found in other studies as well [ 12 , 37 ]. The reason may be that negative results of repeated VCT would provide VCT participants a false sense of security to some extent.…”
Section: Discussionsupporting
confidence: 86%
“… 13 Still on the HIV theme, Ugandanauthors report results of a study on HIV counselling and testing among clients presenting at a market HIV clinic in Kampala. 14 Next we have a paper on adherence to ART, 15 decentralization of ART management, 16 and influence of faith based organizations on HIV prevention. 17 One paper documents HBV DNA gene polymorphisms prediction of chronic HBV infection in India.…”
Section: Infectious Diseasesmentioning
confidence: 99%